2008
DOI: 10.1016/j.eplepsyres.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The novel antiepileptic drug carisbamate (RWJ 333369) is effective in inhibiting spontaneous recurrent seizure discharges and blocking sustained repetitive firing in cultured hippocampal neurons

Abstract: SummaryThis study was initiated to investigate effects of the novel neuromodulator carisbamate (RWJ 333369) in the hippocampal neuronal culture model of status epilepticus and spontaneous epileptiform discharges. Whole-cell current clamp techniques were used to determine the effects of carisbamate on spontaneous recurrent epileptiform discharges (SREDs, in vitro epilepsy), depolarization-induced sustained repetitive firing (SRF) and low Mg 2+ -induced continuous high frequency spiking (in vitro status epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(61 reference statements)
3
15
0
Order By: Relevance
“…We used neurons 24 h after 3 h exposure to low-Mg 2+ solution in this HNC model of AE, in which condition hippocampal neurons develop SREDs with high-frequency spike firing >3 Hz [25]. The two in vitro models are amenable to experimental manipulation, allow for direct analysis of neurons undergoing SREDs and SE in vitro and are valuable tools for the pharmacological studies on the anticonvulsant effects of various investigational compounds [22], [33].…”
Section: Discussionmentioning
confidence: 99%
“…We used neurons 24 h after 3 h exposure to low-Mg 2+ solution in this HNC model of AE, in which condition hippocampal neurons develop SREDs with high-frequency spike firing >3 Hz [25]. The two in vitro models are amenable to experimental manipulation, allow for direct analysis of neurons undergoing SREDs and SE in vitro and are valuable tools for the pharmacological studies on the anticonvulsant effects of various investigational compounds [22], [33].…”
Section: Discussionmentioning
confidence: 99%
“…One study has successfully used pharmacological intervention following injury in the in vitro low Mg 2+ model of SE to prevent the development of SREDs [81]. It was demonstrated that a new anticonvulsant drug [82,83], carisbamate, also exhibited anti-epileptogenic properties in vitro in hippocampal cultures [81]. This means that the drug was able to prevent the development of SREDs when given following in vitro SE and that it did not have to be present in the culture media for the SRED-free activity to persist, differentiating it from most anticonvulsants.…”
Section: Expert Commentarymentioning
confidence: 99%
“…1) is a novel neuromodulator with a broad range of anticonvulsant activity (ED 50 5-60 mg/ kg) in rodent seizure models that is under development by Johnson & Johnson Pharmaceutical Research and Development, for the treatment of epilepsy (Deshpande et al, 2008;Rogawski, 2006;Novak et al, 2007;Mannens et al, 2007). Despite its relatively simple structure, there are few synthetic approaches for the target compound reported in the literature.…”
Section: Introductionmentioning
confidence: 99%